Antimicrobial peculiarities of modified magnesium alloy in vitro - Chorny, Vadim; Yatsun, Yevgen; Polishchuck, Nataliya; Kamyshnyі, Аleksandr; Golovakha, Maksim (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Infection complications after osteosynthesis happen in 5,3–75,4 % of cases, among them posttraumatic osteomyelitis — in 3–24 % after open and 1–7 % — after surgery of closed fractures. The main infectious agents of surgical site infection are Staphylococcus species. Objective: to assess antimicrobial activity of disintegration products of modified magnesium alloy ML-10 as for S. aureus. Methods: in the experiment we used modified magnesium alloy ML-10 with modulus of elasticity which is close to cortex bone surface (≈45 GPа) in the form of shavings (0,5 and 1 mg), discs (weight 125 mg, diameter 5 mm, height 3 mm) and cylinders (weight 750 mg, diameter 5 mm, length 18 mm). Shavings and discs were placed into test tubes with Mueller-Hinton broth (рН 7,4), and discs and cylinders — into Mueller-Hinton agar. As test microbial agent we used culture of standard reference S. aureus ATCC 25923 (American Type Culture Collection). Results: it was shown that products of disintegration of modified magnesium alloy ML-10 have bacteriostatic effect and significant antimicrobial activity as for test infection agent S. aureus ATCC 25923, they suppress its growth in liquid environment during three days. Such effect was conducted by products of disintegration of mentioned alloy due to electric and chemical reactions and creation of alkaline PH environment (from 7,4 to 9,6). Disintegration products of modified magnesium alloy ML-10 can diffuse in dense nutrient and suppress the growth of S. aureus. Conclusions: it was confirmed that modified magnesium alloy ML-10 can be used for implant production. There is unique possibility to prevent the growth of S.aureus which is the main infection agent of implant-associated infection.